2014
DOI: 10.1080/0144929x.2014.912353
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cognition and affect: sensing the unconscious

Abstract: In the past decade, research on human-computer interaction has embraced psychophysiological user interfaces that enhance awareness of computers about conscious cognitive and affective states of users and increase their adaptive capabilities. Still, human experience is not limited to the levels of cognition and affect but extends further into the realm of universal instincts and innate behaviors that form the collective unconscious. Patterns of instinctual traits shape archetypes that represent images of the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Therefore, the comparison is problematic. Another study by Ivonin, et al [ 69 ] reported higher accuracies of predicting archetypal experiences but it used within-subjects models for classification, and moreover, fell short in conducting statistical comparison of classification accuracies obtained for different conditions. In order to have a relative benchmark, the results obtained for the explicit emotions can be set against previous studies that dealt with recognition of affect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the comparison is problematic. Another study by Ivonin, et al [ 69 ] reported higher accuracies of predicting archetypal experiences but it used within-subjects models for classification, and moreover, fell short in conducting statistical comparison of classification accuracies obtained for different conditions. In order to have a relative benchmark, the results obtained for the explicit emotions can be set against previous studies that dealt with recognition of affect.…”
Section: Discussionmentioning
confidence: 99%
“…Developments in affective computing (Tao and Tan 2005) can monitor physiological responses (Ivonin et al 2015) to infer users' emotional states. Other techniques examine the text users employ for sentiment analysis (Balci and Salah 2015;Colace et al 2015;Ortigosa, Martin, and Carro 2014), consider dwell times (Strebe 2016), or examine keystroke dynamics (Nahin et al 2014), or mouse clicks (Macaulay 2004) to infer emotional states.…”
Section: Consumer Trackingmentioning
confidence: 99%
“…As a variety of systems are being developed to infer emotional state (e.g. Ivonin et al 2015;Macaulay 2004;Nahin et al 2014;Tao and Tan 2005), the consideration of response to a win or loss is thus timely. The present study indicates that people are more likely to respond to advice when experiencing loss, and there are indications that receptivity may also vary dynamically as circumstances change.…”
Section: Contingencymentioning
confidence: 99%
“…Regarding the unconscious emotions in media content, some preliminary studies have revealed that specific narratives in media content would induce unique physiological patterns while the audience is unaware of it (Ivonin et al , 2014(Ivonin et al , 2015Chang et al 2014b). It is promising to explore further with this direction.…”
Section: Potential Challenges and Promising Approachesmentioning
confidence: 99%